Detecting concentrations of milk components by an iterative optical technique. Issue 11 (26th February 2015) - Yariv, Inbar; Kapp‐Barnea, Yaara; Genzel, Eran; Duadi, Hamootal; Fixler, Dror
Abstract : This paper introduces a theoretical and practical model for reconstructing the scattering properties of a participating media. Our theory is based on a robust generalization of the Gerchberg–Saxton (G–S) algorithm. At the end of this algorithm the reduced scattering coefficient μ′ s of a given substance, can be estimated from the standard deviation (STD) of the retrieved phase of the remitted light. We use the theory to compute the phase's STD that directly correlated to the optical properties for different types of milk components, and we derive a novel appearance model for milk parameterized by the lactose and protein contents. Our results show that we are able to detect the possibility of lactose and milk proteins' quantitative signature by the G–S optical tool, en route to the design of a novel milk‐content‐monitoring tool.Sketch of the experimental setup for light intensity measurements and reduced scattering coefficient reconstruction. The samples were prepared from various milk components: whey protein, sodium casienate and lactose, at different concentrations. Abstract : Milk contents analyses however challenging, are essential in the dairy food industry to define milk value for quality control and the upturn of cow health and milk yield. We suggest the utilization of a novel optical technique for milk contents determination. The technique, based on Gerchberg‐ Saxton (G‐S) algorithm, was able to detect the possibility of lactose and milk proteins' quantitative signature, en‐route to the design of a novel milk content monitoring tool.